Weather Index Based Insurance for the Pacific - Maher, Barry; McCaffrey, Michael (Technical Centre for Agricultural and Rural Cooperation, 2018)
Smallholder farmers in the Pacific have no access to weather index-based insurances, while flooding is a real threat for them. Preliminary research in the region suggests that weather and agricultural data, and the exact locations of farmers is weak in the region.